One-Way Self-Expanding Rod in Neuromuscular Scoliosis: Preliminary Results of a Prospective Series of 21 Patients. Issue 4 (October 2021) - Gaume, M.; Hajj, R.; Khouri, N.; Johnson, M.B.; Miladi, L.
Abstract : Background: Fusionless techniques for the treatment of neuromuscular early-onset scoliosis (EOS) are increasingly used to preserve spinal and thoracic growth and to postpone posterior spinal fusion (PSF). These techniques have greatly improved thanks to magnetically controlled growing rods, which allow the avoidance of repeated surgery. However, the surgery-related complication rate remains high. The objective of the current study was to report the preliminary outcomes of 21 patients with neuromuscular EOS who were treated with a 1-way self-expanding rod (OWSER). This device was designed to avoid repeated surgery and preserve spinal and thoracic growth thanks to its free rod sliding. Methods: Patients with neuromuscular EOS who underwent OWSER fixation were prospectively reviewed; follow-up was a minimum of 3 years. The instrumentation relies on a bipolar construct from T1 to the sacrum, with proximal fixation by double thoracic hook-claws and distal fixation by iliosacral screws. The device comprises a rod with a notched part sliding in 1 direction inside a domino. Changes in Cobb angle, pelvic obliquity, thoracic kyphosis, lumbar lordosis, T1-S1 and T1-T12 length, space available for the lung, and chest width were assessed. Complications were reviewed. Results: The mean age at surgery was 10.5 years. The mean follow-up was 3.9 years. The mean pelvic obliquity improved from 20° preoperatively to 8° postoperatively and to 6° at the latest follow-up. The mean Cobb angle improved from 66° preoperatively to 38° postoperatively and to 32° at the latest follow-up. The mean preoperative kyphosis was reduced from 41° to 26° at the latest follow-up (p = 0.14). The mean lordosis was 34° preoperatively and 38° at the latest follow-up. The mean growth per month was 0.8 mm for the T1-T12 segment and 1.5 mm for T1-S1. The global complication rate was 38% (2 surgical site infections, 3 cases of lack of rod expansion, 1 case of pyelonephritis, and 2 central venous catheter-related infections). No PSF had been performed at the latest follow-up. Conclusions: Use of the OWSER with a minimally invasive bipolar technique for neuromuscular EOS provided satisfactory correction of spinal and pelvic deformities at 3 years of follow-up. A longer follow-up is required. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.